Tooth brushing performance in adolescents as compared to the best-practice demonstrated in group prophylaxis programs: an observational study - Zdenka Eidenhardt; Alexander Ritsert; Sadhvi Shankar-Subramanian; Stefanie Ebel; Jutta Margraf-Stiksrud; Renate Deinzer (BMC, 2021)
Abstract Background Research indicates that adolescents may have difficulties to adopt the tooth brushing recommendations delivered in prophylaxis programs. However, it is not clear whether these difficulties are seen amongst the entire age range of adolescence (10-19 years) or only occur at certain developmental stages of the adolescence. The present study analyzes the tooth brushing performance of adolescents and compares it to the best-practice of tooth brushing demonstrated during prophylaxis programs. Methods A random sample of N = 66 adolescents, comprising 10-year-olds (n = 42) and 15-year-olds (n = 24), were asked to perform oral hygiene to the best of their abilities in front of a tablet camera. Videos were analyzed for tooth brushing duration, location, and brushing movements, and the difference between the actual and expected behaviour was tested for consistency using repeated measures ANOVAs and Student's t-tests. For the direct comparison across different age groups, already available data from 12- and 18-year-olds were reanalysed. Results The average brushing time (mean ± SD) of the 10-year-olds and 15-year-olds was 195.8 s (74.6 s) and 196.1 s (75.8 s), respectively. Regardless of age, the adolescents distributed their brushing time unevenly across the inner, outer and occlusal surfaces. The inner surfaces in particular were neglected to a considerable extent, as no age group spent more than 15.8% of the total brushing time on them. Furthermore, all age groups showed a high proportion of horizontal movements on the inner and outer surfaces, regardless of the movements instructed for the respective surfaces. Conclusion Even if adolescents brush to the best of their abilities, they neglect or skip one or many of the tooth surfaces. The reasons for the lack of compliance to tooth brushing instructions are discussed in light of the methods used in prophylaxis programs and the influence of parents.